Benthic development on large-scale engineered reefs: a comparison of communities among breakwaters of different age and natural reefs - Burt, John (2011)
Breakwaters represent large-scale engineered artificial reefs that can develop diverse and abundant communities and are likely to play an increasing role in marine ecosystems as human populations grow in coastal urban areas. Information on how these communities develop and if and when these communities begin to resemble those on natural hard-bottom habitat is essential for marine management, but is not well understood. In this study, benthic communities on six breakwaters ranging from 1 to 31 years of age were compared to provide an understanding of patterns of community development on engineered coastal defenses, and these were compared to communities on natural reefs to gain an understanding of how communities develop on artificial structures relative to those in natural habitats. Multivariate analyses indicated that benthic communities on breakwaters became more similar to natural reefs with increasing age, but that communities on even the most mature (31 years) breakwater were distinct from those on natural reefs (ANOSIM p < 0.001). Generally, breakwaters ?5.5 years had higher abundance of turf algae, sponges, bivalves, and bare pavement, while more mature (?25 years) breakwaters were dominated by corals. Coral cover on 25 and 31 years old breakwaters (46% and 56%, respectively) was significantly higher than on natural reefs (37%; HSD test p < 0.05 and p < 0.001, respectively). These results indicate that breakwaters develop benthic communities that continue to change over periods exceeding 31 years, and that although they become more similar to communities on natural reefs with increasing age, these communities remain distinct.